Impact of Lean Manufacturing Practices on Sustainable Firm Performance: An Empirical Study Moderated by Lean Culture - Bilal Hassan; Urooj Pasha (International Journal of Business and Economic Affairs, 2023)
The main objective of this empirical study is to investigate the impact of lean manufacturing practices (total quality management and just in time) on firm’s sustainability performance in leather export industry of Pakistan, moderated by the lean culture of the firm. Also, we measure the level of moderation created by lean culture in lean system to achieve the sustainability in firm performance. Study used the empirical research study by adopting quantitative research methodology to collect the required data to gain results on set objectives and research questions. Data collected through the various level of executives, managers and supervisors of the leather export industry of Pakistan. A 240 final sample utilized in data processing to check the stated research questions and objectives. Stratified random sampling technique used to analyses the data and from each stratum, a random sample selected from each stratum. This study finding are in accordance with the prior studies of literature which shows the significant impact of lean manufacturing on firm’s sustainability performance. Results shows the firms main focused on process efficiency and enhancing productivity by eliminating wastes at each level, firms used this approach as competitive advantage having highly focus on preferences required by customer, which is usually, “quality product, low cost, maximum variety with efficient delivery”. This study also provides the insightful managerial implications and future directions in the fields of lean sustainability.